Biomass and Carbon Inventore of Teak (Tectona grandis L.f.) in the Community Forest of Jatimulyo Village, Karanganyar - Ris Hadi Purwanto; Melikaries Silaban (Jurnal Ilmu Kehutanan)
Forests store biomass and carbon in the form of living trees, forest floor detritus (e.g. litter falls), soil and wood products. This study describes inventory results of the above ground biomass of teak (Tectona grandis L.f.) in the community forest of Jatimulyo Village, Karanganyar District. By developing allometric method, the inventory was designed to estimate the potential of above ground biomass of teak in the community forest. To establish the allometric equations, 410 sample trees were measured to determine the relationships between tree height (H) and diameter of breast height (D). Ten trees of various sizes were cut to measure the above ground biomass (stem, branch and leaves). The results showed that diameter at breast height ( about 1.3 m above the ground, D) was a good predictor of tree height (H) with r2 more than 0.8886. When D was combined with H, r2 was improved somewhat for the stem, branch and total above ground biomass, suggesting the growth patterns of tree dimensions were closely interdependent. Carbon storage of the teak forests was based on the assumption that carbon (C) concentration was 50% of the biomass. A standing stock of the above ground biomass of teak in the community forests of Jatimulyo Village was then inventoried based on the allometric relations. Results showed that the above ground biomass of teak in these community forests were 27.064 ton/ha, equal to 13.532 ton carbon/ha, with a basal area of 6.1526 m2/ha. Based on the carbon stock and basal area, the teak community forests of Jatimulyo Village are categorized as having low stand potential.